AGENCY PROBLEM PADA SAAT RIGHT ISSUE - Hartini Hartini (Media Riset Bisnis & Manajemen, 2001)
Agency Problem is a potential confict interest between shareholders and manag- ers. Managers are agents of shareholders, they will take corporate actions that maximize their own utility, such as right issue, they made a right issue announce- ment because they require much money to make an investment or to expand the firm. These actions will not necessarily be consistent with firm value maximization. The shareholders want the fund to be paid as dividends. Theoretically, right issue announcement will be met with a negative shareholders reaction, which mean the stock price will decrease after the announcement of rightissue. The objective of this research is to verify empirically the existence of agency problem when right issue announcement. This research examines 63 firms that made right issue announce- ment. In the other hand, this research also examines 20 firms from banking sector made right issue announcement in Jakarta Stock Exchange during 1998 to June 2001. The analysis method is using Market Model, that apply to estimate the stock performances are market return, stock return, beta, alpha, abnormal retum and cumulative abnormal retum. Overall, the results of this research indicate that agency problem haven't happened when right issue announcement, because there are no significant differences statistically among cumulative abnomal retum before and after right issue announcement.